Analyzing the Influence of Bank Competition on Credit Risk: Perspectives from Indonesia's Dual Banking System - Febriana, Adella; Suhel, Suhel; Andaiyani, Sri (Jurnal Ekonomi Kuantitatif Terapan; Vol 17 No 1 (2024): Vol. 17, No. 1, Februari 2024 (pp.1-154), 2024)
This study analyzes the effect of competition banks on credit risk in the dual banking system in Indonesia. This research was conducted using a purposive sampling technique in selecting a sample of 5 conventional commercial banks and 5 Islamic commercial banks. The method used is the Generalized Method of Moments (GMM) from 2011 to 2020. Credit risk for Conventional Banks is measured by the value of Non-Performing Loan (NPL), while Islamic Bank Financing is measured by the value of Non-Performing Financing (NPF). The results of this study indicate that Return on Assets (ROA) for Conventional Banks and Islamic Banks has a significant effect on credit risk in the dual banking system, Loan to Deposit Ratio (LDR) for Conventional Banks does not have a significant effect on Non-Performing Loan (NPL) while Financing to Deposit Ratio (FDR) of Islamic Banks has a significant level 2 influence on Non-Performing Financing (NPF). Bank size does not have a significant influence on credit risk in the dual banking system, and the Lerner Index for Conventional Banks has a significant effect on Non-Performing Loan (NPL), while the Lerner Index for Islamic Banks has no effect on Non-Performing Financing (NPF). The Central Bank in making policies can see that the level of competition for banks in the dual banking system in Indonesia is categorized as a monopolistic competition market, where each bank has its own market segment so that it has market power that is strong enough to set prices that are relatively.